FAMILIEN: Diskurs og deltagelse i dagens Tyrkiet - Mortensen, Lotte Bøggild (Tidsskriftet Antropologi, 1998)
Lotte Bøggild Mortensen: The Family. Discourse and Participation in Today’s Tur key The present article deals with the notion of the family, and the changing forms of patriarchy and male dominance in Turkish society. The empirical data originale from a relatively well to do middle class apartment building in Ankara. Whereas several contemporary studies with a focus on village life and/or poor areas demonstrate how women manipulate within horders set by men, few studies have focused on how wealthy urban families which are commited to Kemalism, interact within the nation-state ideology of the Turkish Republic. The prevalence of Kemalism since 1923 meant the creation of a new role model for women encouraging women to enter public space. This article, however, aims to show that Atatiirk, the founder of Kemalism, had no possibility for - nor was interested in - changing the private or domestic status of women. The urban women in this study nevertheless east their identities for public participation within the Kemalist ideology. The patriarchal definition of Islam forms the local ideology, while the local discourse is shaped and reshaped with due reference to the notion of “naturalizing” male power. Using concepts like speech, silence, eyesight, order and participation, this article shows how women in urban households negotiate male power within the framework of the patriarchal family.